2016
DOI: 10.1039/c6dt01191h
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of uranyl ions from bulk of thorium(iv) and lanthanide(iii) ions by tetraalkyl urea: a combined experimental and quantum chemical study

Abstract: The selective separation of uranyl ions from an aqueous solution is one of the most important criteria for sustainable nuclear energy production. We report herein a known, but unexplored extractant, tetraalkyl urea, which shows supreme selectivity for uranium in the presence of interfering thorium and other lanthanide ions from a nitric acid medium. The structural characterization of the uranyl complex (UO2X2·2L, where X = NO3(-), Cl(-) and Br(-)) by IR, NMR and single crystal X-ray diffraction provides insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…After uranyl ion addition, there was no shift in −NH 2 and −OH stretching frequencies with respect to that of reline, which suggested no direct bonding of either −NH 2 or −OH groups of urea and choline chloride, respectively, with uranyl ion. However, the carbonyl stretching frequency is shifted to ∼42 cm –1 downward from 1660 to 1618 cm –1 , indicating a direct interaction of the uranyl group with the carbonyl group of urea. Peaks observed at ν = 1472 cm –1 (CH 3 ), 1081 cm –1 (CH 2 ), 1005 cm –1 (ν COH), 952 cm –1 (ν as CCO), and 864 cm –1 (ν s N–CH 3 ) in reline and uranyl-added reline confirmed that the choline groups remain unaffected . There were additional peaks at 920 and 830 cm –1 in uranyl-added reline which correspond to the asymmetric (ν as ) and symmetric stretching (ν s ) of UO 2 2+ group, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…After uranyl ion addition, there was no shift in −NH 2 and −OH stretching frequencies with respect to that of reline, which suggested no direct bonding of either −NH 2 or −OH groups of urea and choline chloride, respectively, with uranyl ion. However, the carbonyl stretching frequency is shifted to ∼42 cm –1 downward from 1660 to 1618 cm –1 , indicating a direct interaction of the uranyl group with the carbonyl group of urea. Peaks observed at ν = 1472 cm –1 (CH 3 ), 1081 cm –1 (CH 2 ), 1005 cm –1 (ν COH), 952 cm –1 (ν as CCO), and 864 cm –1 (ν s N–CH 3 ) in reline and uranyl-added reline confirmed that the choline groups remain unaffected . There were additional peaks at 920 and 830 cm –1 in uranyl-added reline which correspond to the asymmetric (ν as ) and symmetric stretching (ν s ) of UO 2 2+ group, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…The above methodology was earlier reported to produce good correlation with the experimental results. [54][55][56] Finally, binding free energy of the metal binding reactions was calculated using following reaction scheme:…”
Section: Computational Protocolmentioning
confidence: 99%
“…The original concept of this precipitation‐based method is strongly related to yellowcakes such as diuranate salts or uranyl peroxide , . Even today, there are also several research activities of precipitation‐based reprocessing or separation methods with similar concept to ours …”
Section: Introductionmentioning
confidence: 99%